Influence of temperature and light conditions on dormancy break and germination of the Mediterranean endemism of Scilla paui and Scilla ramburei (Liliaceae) - Santiago, Alejandro; Herranz, José Mª; Copete, Miguel Ángel; Herranz, Raquel; Ferrandis, Pablo (BOSQUE, 2017)
We studied the germination ecology of Scilla paui and Scilla ramburei to check the existence of underdeveloped embryos, as well as to verify the presence of any physiological or morphophysiological dormancy levels described for the family Liliaceae. Seeds of S. paui had fully developed embryos at seed dispersal and they were physiologically dormant. After eight weeks of cold (5 ºC) stratification followed by a four-week incubation at 15/4 ºC in darkness, germination was 100 %. This record, along with the promotion of germination mediated by gibberellic acid, pointed out that seeds of S. paui had non-deep physiological dormancy. In S. ramburei seeds, the average embryo length at dispersal was 1.60 mm; they had to grow to the critical length of 2.14 mm to be able to germinate. Embryo growth and radicle emergence occurred after seed exposure to a sequence of temperatures typical of the end summer-beginning autumn period. Emerged radicles required two months of exposition to winter cold (5 ºC) for seedling emergence in February and March. Seeds of S. ramburei had deep simple epicotyl morphophysiological dormancy. The differences detected in the germination ecology support the segregation of both taxa as different species, and suggest the convenience of taking into account physiological traits in systematic studies.